Artificial Intelligence in Libraries: Prospect and Challenges for Nigerian Academic Libraries - Idemudia, Blessing Ehinomhen; Makinde, Bosede (Communicate: Journal of Library and Information Science, 2022)
Artificial Intelligence is now being applied with evidence in all facets of life, in the academic, health, economic sectors as well as in the library for efficiency and effectiveness. This study focused on the application of Artificial intelligence in libraries: prospects and challenges for Nigerian Academic Libraries. It was centered on how, and which areas in the library that artificial intelligence could be applied. It was found that artificial intelligence have different component such as the expert system, pattern recognition, natural language processing, as well robotics, and these different components of AI can be applied in Nigeria Academic libraries. For example, they could be applied in the area of acquisition of library materials, cataloguing, classification, indexing etc. Literature surveyed equally revealed that robotics is an example of artificial super intelligence with advantages that could revolutionize service delivery in academic libraries. Nigeria Academic libraries could use artificial intelligence in its operations irrespective of the challenges that may pose as barriers, because AI ensures efficiency, effectiveness and quality library service delivery.